Substansmisbruikers se sensoriese prosessering, woede-ervaringe en -gedrag - Crous, Denisé (University of the Free State, 2009)
Various patients with mental health disorders display problematic anger experiences and anger behaviour (DiGuiseppe & Tafrate, 2007:9). Many people with high anger tendencies appear to abuse substances on regular basis (Tafrate et al., 2002:1585). It seems as if the sensory processing patterns of substance abusers are clinically significant (Quadling et al., 1999:12). Sensory processing is reflected in people’s moods, temperament and ways in which they organise their lives (Dunn, 2001:609). Relationships between sensory processing, anger experiences and anger behaviour were investigated in substance abusers, using a quantitative cross-sectional research design. The Ethics Committee of the Faculty of Health Sciences, University of the Free State, approved the study. (ETOVS nr. 133/08). Data was collected between 1 October 2008 en 29 May 2009 at Stabilis Treatment Centre and Denmar Specialist Psychiatric Hospital. The study was piloted at both institutions and these results were included into the study’s results. Eighty four in-patients, with a history of substance abuse, voluntarily participated in the study. Convenience sampling was used and the majority of participants spoke Afrikaans (64%), were male (68%) and had abused alcohol (66%). Participants’ average age was 36 years and 6 months. The participants completed three questionnaires. Questionnaire one collected demographic information. Participants’ sensory processing was assessed through completing the Adolescent/Adult Sensory Profile. The anger questionnaire was compiled, based on indicators from literature and assessed the intensity of anger experiences in situations related to sensory processing behaviours and the frequency of anger behaviour. Anger behaviour was investigated with regards to: expressing anger verbally, expressing anger physically, withdrawing from the angering situation, using substances when experiencing anger, suppressing anger, expressing anger non-verbally and applying calming strategies. Department Biostatistics, University of the Free State, analysed the data of the study. According to the results it appeared as if participants’ could experience high intensity levels of anger in situations related to their: • low registration behaviour more than the typical norm, in vestibular, visual and auditory processing, • sensory sensitive behaviour more than the typical norm, in vestibular, touch and auditory processing and • sensory avoiding behaviour more than the typical norm in touch and auditory processing, as well as activities that did not provide for sensory avoiding behaviours. The results further indicated that participants with low registration patterns more than the typical norm of this quadrant, regularly used substances when they were angry and regularly expressed their anger verbally and physically. With regards to participants with sensory avoiding patterns more than the typical norm of this quadrant, results indicated that they regularly withdrew from angering situations, suppressed their anger, expressed their anger non-verbally, applied calming strategies and used substances when experiencing anger. A need for further research was indicated with regards to the relationships between sensory seeking patterns and anger behaviour. Ongoing research with regards to adult clinical populations’ sensory processing appears to be worthwhile. Occupational therapists should consider assessing their adult patients, with problematic anger (like substance abusers), sensory processing and if necessary integrate it into treatment.
Dissertation (M.Occupational Therapy (Occupational Therapy))--University of the Free State, 2009
Keywords: Substance abuse -- Psychological aspects; Anger; Senses and sensation -- Testing; Sensorimotor integration -- Testing; Occupational therapy; Sensory processing; Behaviour